2021
DOI: 10.1186/s12864-021-07997-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide associations for immune traits in two maternal pig lines

Abstract: Background In recent years, animal welfare and health has become more and more important in pig breeding. So far, numerous parameters have been considered as important biomarkers, especially in the immune reaction and inflammation. Previous studies have shown moderate to high heritabilities in most of these traits. However, the genetic background of health and robustness of pigs needs to be extensively clarified. The objective of this study was to identify genomic regions with a biological rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 73 publications
(118 reference statements)
2
19
0
Order By: Relevance
“…Making use of highly informative genotype data, genome-wide association studies (GWAS) that use highly informative genotypes are a highly efficient approach to map loci and to detect QTL and candidate genes for complex traits (e.g., [ 1 ]). This approach enables fine mapping [ 19 ] and validation of previously identified regions in a GWAS for important traits (e.g., [ 21 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Making use of highly informative genotype data, genome-wide association studies (GWAS) that use highly informative genotypes are a highly efficient approach to map loci and to detect QTL and candidate genes for complex traits (e.g., [ 1 ]). This approach enables fine mapping [ 19 ] and validation of previously identified regions in a GWAS for important traits (e.g., [ 21 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Selection was conducted by applying several theoretical concepts and approaches under practical conditions. Selection steps were built on existing pedigree and real SNP genotype information within the pigFit project which focuses on piglet survival and immunocompetence [ 20 , 21 ]. Performance of the different selection strategies was assessed based on the accuracy of imputation of masked genotypes from SNP chip data.…”
Section: Introductionmentioning
confidence: 99%
“…Data sets of purebred LR and LW subset pig populations were recorded from 2010 to 2017 and were provided by the German breeding organization BHZP GmbH as already been described in Dauben et al (2021). The animals within the nucleus populations were kept under high hygienic conditions and reflect the genetic diversity of both populations concerning their different breeding objectives.…”
Section: Animals and Phenotypic Measurementsmentioning
confidence: 99%
“…Additionally, hematological characteristics are crucial traits that are associated with immune and metabolic status and diseases in pigs. Previous studies have reported that many blood parameters are heritable in swine [ 10 , 11 ], and serval genes have been identified by GWAS, RNA-seq, and eGWAS in pigs [ 12 , 13 , 14 ]. China has long been regarded as the largest live pig and pork consumption country in the world, and the per capita pork consumption is about 20 kg.…”
Section: Introductionmentioning
confidence: 99%